Antileishmanial activity of Melampodium divaricatum and Casearia sylvestris essential oils on Leishmania amazonensis - Moreira, Raquel Regina Duarte [UNESP] (2019)
Leishmaniasis is a disease that affects millions of people and it is an important public health problem. The drugs currently used for the treatment of leishmaniasis present undesirable side effects and low efficacy. In this study, we evaluated the in vitro activity of Melampodium divaricatum (MD-EO) and Casearia sylvestris (CS-EO) essential oils (EO) against promastigote and amastigote forms of Leishmania amazonensis. Sesquiterpenes E-caryophyllene (56.0%), germacrene D (12.7%) and bicyclogermacrene (9.2%) were identified as the main components of MD-EO, whereas E-caryophyllene (22.2%), germacrene D (19.6%) and bicyclogermacrene (12.2%) were the main constituents of CS-EO. CS-EO and E-caryophyllene were active against promastigote forms of L. amazonensis (IC50 24.2, 29.8 and 49.9 µg/mL, respectively). However, MD-EO, CS-EO and E-caryophyllene were more active against amastigote forms, with IC50 values of 10.7, 14.0, and 10.7 µg/mL, respectively. E-caryophyllene presented lower cytotoxicity against macrophages J774-A1 (CC50 of 62.1 µg/mL) than the EO. The EOs and E-caryophyllene should be further studied for the development of new antileishmanial drugs.